Improving Social Cognition in People with Schizophrenia with RC2S: Two Single-Case Studies - Peyroux, Elodie; Franck, Nicolas (Frontiers in Psychiatry, 2016)
Difficulties in social interactions are a central characteristic of people with schizophrenia, and can be partly explained by impairments of social cognitive processes. New strategies of cognitive remediation have been recently developed to target these deficits. The RC2S therapy is an individualized and partly computerized program through which patients practice social interactions and develop social cognitive abilities with simulation techniques in a realistic environment. Here we present the results of two case studies involving two patients with schizophrenia presenting with specific profiles of impaired social cognition. Each patient completed three baseline sessions, 14 treatment sessions, and three follow up sessions at the end of the therapy – and for one patient, another three sessions nine months later. We used a multiple baseline design to assess specific components of social cognition according to the patients’ profiles. Functioning and symptomatology were also assessed at the end of the treatment and six months later. Results highlight significant improvements in the targeted social cognitive processes and positive changes in functioning in the long term. The RC2S program seems thus to be a new useful program for social cognitive remediation in schizophrenia.